PORTRAIT DE FRANCIS SANCHER ; PORTRAIT DE RIVIERE AU SEL : APPORT DES VOIX ET DES TEMOIGNAGES POLYVALENTS - Jatoe-Kaleo, Baba Abraham (European Scientific Journal, ESJ, 2013)
Abstract In Crossing the Mangrove Maryse CondÃ© uses two narrative voices distributed among several narrative perspectives: the impersonal, historic and â€œobjectiveâ€ voice mediated by the third-person narrative voice and mainly monopolized by male narrators; and the subjective first person-narrative voice left to female narrators and marginalised male voices such as Xantippe and Moses. The narrative of the latter group is endowed with some credibility. This way CondÃ© succeeds in decentring and de-hierarchising the use of the third person narrative voice as the most preferred instance for transmitting reliable information. The third-person narrative voice is thus brought to the level of the first-person narrative: the accounts of all the characters therefore combine to make the story of Sancher inscrutable, impartial and exact. The narrative in Crossing in this way consigns to futility the quest for any pure linearity of ascendance; of any identity based on the idea of pure stock. This kind of quest leads to death. The association of the citizens of River of salt to Sancher at his death makes of him a figurative representation of this society, and by extension of the whole world.